Development and Evaluation of an Edutainment Tool for Imparting Education and Awareness among Type 1 Diabetes Children in Qatar - Abdulla Al Hamaq; Ahmed A Elasyouti; Rasha T Abou-Amona; Nedaa G ElKhatib (Journal of Diabetology)
Abstract Background: Appropriate initial education for type 1 diabetes mellitus (T1DM) is important to prevent late complications. However, type 1 children with diabetes do not appreciate traditional learning methods since they rarely contain the elements of fun and interactivity. In this study, we developed, implemented, and evaluated an edutainment tool for the initial education of type 1 children with diabetes. Materials and Methods: The Health Park pack is an edutainment tool that contains three games, two board games “The Health Park, Slides & Ladders” and one card game “Match-Up.” The games were designed to provide essential information about food, exercise, and insulin. A total of 46 children with T1DM evaluated the degree of entertainment, usability, and clinical usefulness of the games with the structured questionnaire. Results: More than 95% of T1DM children showed interest in the edutainment approach as the game was useful for initial education for T1DM. More than 90% agreed that they had fun playing the game, and 68% agreed to play the game again. The majority of them recommended the game to friends with diabetes and friends without diabetes. Conclusion: Using games could be an interesting edutainment tool for children with T1DM to motivate and educate them.